STABILISASI TANAH LEMPUNG DENGAN PENAMBAHAN LIMBAH SAWIT TERHADAP NILAI CALIFORNIA BEARING RATIO - Ibrahim Ibrahim (PILAR, 2013)
Soil material that is very influential in the construction work, as an area of land will not have the same properties with other regions. Most areas in Indonesia, especially the city of Palembang on soft ground. Two main problems in soft soil is a huge drop and land carrying capacity is small. Strong bearing clays is strongly influenced by the water content, which when dry soil conditions have a strong high capacity and soil saturation conditions will have a lower carrying capacity. Large volume changes which can harm the soil so that the buildings need serious treatment. One soil improvement efforts is by using the additive stabilization of solid waste palm kernel. In this study the soil to be stabilized is clay derived from the Tanjung Api-Api, with the addition of the percentage of additive variation of solid waste palm kernel at 2.5%, 5%, 7.5%, 10% and 12.5% . The testing performed is testing soil physical properties (water content, grain grading, soil density, hydrometer analysis and Atterberg limits), and testing of mechanical properties of soil ie CBR (California Bearing Ratio). Percentage obtained in the research process LL value (65.19%) PL (34.90%) and IP (30.29%) while the percentage of the value of the fine fraction sieving size <0.075 mm (93.685%), and the size of the coarse fraction .0.075 mm (1.53%). Results of each percentage value according to the classification system USCS (Unified soil classification system) is included in the clay soil classification group OH ie organic clay with high plasticity to moderate. The addition of the additive causes soil properties LL (liquid limit) PL (plastic limit) increases so that IP (plasticity index) increases. The addition of the additive will affect the percentage of the value of the soaked and unsoaked CBR test. CBR value increased 7.5% and the percentage decrease in the percentage of 10% and 12.5%.